Tourismmorphosis : Badung, Banyuwangi and Luwu Timur Regency (Tourism Evolution Analysis) - I Gusti Agung Oka Mahagangga; I Putu Anom; I Made Kusuma Negara (Udayana Journal of Social Sciences and Humanities, 2019)
Tourismmorphosis in Badung regency, Banyuwangi regency and Luwu Timur regency is field research to understanding developing of tourism as tourism evolution analysis. Tourismmorphosis analyzed was postmodern evolution approach with case study and qualitative methods to find tourism developing stages. Begin from the introduction stage, reaction stage, institutionalization stage and compromise stage. The research novelty described that Badung Regency having reached the compromise stage, Banyuwangi Regency reached the institutionalization stage and Luwu Timur regency just started to the introductory stage. The prediction of tourism development future in Badung regency will permanent at the compromise stage, Banyuwangi Regency stay at the institutionalization stage, and Luwu Timur district will enter the reaction stage within ten until fifteen years letters.